High Altitude Increases Alteration in Maximal Torque but Not in Rapid Torque Development in Knee Extensors after Repeated Treadmill Sprinting - Girard, Olivier; Brocherie, Franck; Millet, Grégoire P. (Frontiers in Physiology, 2016)
We assessed knee extensor neuromuscular adjustments following repeated treadmill sprints in different normobaric hypoxia conditions, with special reference to rapid muscle torque production capacity. Thirteen team- and racquet-sport athletes undertook 8 x 5-s “all-out” sprints (passive recovery = 25 s) on a non-motorized treadmill in normoxia (NM; FiO2 = 20.9%), at low (LA; FiO2 = 16.6%) and high (HA; FiO2 = 13.3%) normobaric hypoxia (simulated altitudes of 1800 m and 3600 m, respectively). Explosive (∼1 s; “fast” instruction) and maximal (∼5 s; “hard” instruction) voluntary isometric contractions (MVC) of the knee extensors, with concurrent electromyographic (EMG) activity recordings of the vastus lateralis (VL) and rectus femoris (RF) muscles, were performed before and 1-min post-exercise. Rate of torque development (RTD) and EMG (i.e., Root Mean Square or RMS) rise from 0 to 30, -50, -100 and -200 ms were recorded, and were also normalized to maximal torque and EMG values, respectively. Distance covered during the first 5-s sprint was similar (P>0.05) in all conditions. A larger (P<0.05) sprint decrement score and a shorter (P<0.05) cumulated distance covered over the eight sprints occurred in HA (-8±4% and 178±11 m) but not in LA (-7±3% and 181±10 m) compared to NM (-5±2% and 183±9 m). Compared to NM (-9±7%), a larger (P<0.05) reduction in MVC torque occurred post-exercise in HA (-14±9%) but not in LA (-12±7%), with no difference between NM and LA (P>0.05). Irrespectively of condition (P>0.05), peak RTD (-6±11%; P<0.05) and normalized peak RMS activity for VL (-8±11%; P=0.07) and RF (-14±11%; P<0.01) muscles were reduced post-exercise, whereas reductions (P<0.05) in absolute RTD occurred within the 0-100 (-8±9%) and 0-200 ms (-10±8%) epochs after contraction onset. After normalisation to MVC torque, there was no difference in RTD values. Additionally, the EMG rise for VL muscle was similar (P>0.05), whereas it increased (P<0.05) for RF muscle during all epochs post-exercise, independently of the conditions. In summary, alteration in repeated-sprint ability and post-exercise MVC decrease were greater at high altitude than in normoxia or at low altitude. However, the post-exercise alterations in RTD were similar between normoxia and low-to-high hypoxia.